Effect of cover management factor in quantification of soil loss: case study of Sungai Akah subwatershed, Baram River basin Sarawak, Malaysia - Hamza, Vijith; Seling, L.; Dodge-Wan, Dominique (Taylor & Francis Ltd., 2017)
© 2017 Informa UK Limited, trading as Taylor & Francis Group The present study evaluates the effectiveness and suitability of cover management factors (C factor) generated through different techniques like land use/land cover-based arbitrary value (C LULC ), Normalised Different Vegetation Index-based methods C NDVI1 and C NDVI2 and Modified Soil Adjusted Vegetation Index 2-based method (C MSAVI2 ). The C factors generated using these four methods were tested in the calculation and assessment of annual average soil loss from an upland forested subwatershed in the Baram river basin using the Revised Universal Soil Loss Equation (RUSLE). The four cover management factor maps generated by this analysis show some variation among the results. The LULC method uses a single arbitrary value for each LULC type mapped in the subwatershed. The other three methods show a range of C values within each mapped LULC type. The effects of these variations were tested in the RUSLE by keeping the factors such as rainfall erosivity (R), soil erodibility (K), slope-length and steepness (LS) constant. The maximum annual average soil loss is 1191 t. ha -1 . y -1 based on the C LULC . Soil losses estimated with other three methods are very different compared to those estimated with the C LULC method. The highest calculated soil loss values were 1832, 1674 and 1608 t. ha -1 . y -1 in the study area based, respectively, on C NDVI1 , C NDVI2 and C MSAVI2 C factors. These maximum values represent the worst pixel scenario values of soil loss in the region. The statistical analysis performed indicates different relationship between the parameters and suggests the acceptance of the methodology based on C NDVI2 for the study area, instead of a single value method such as C LULC . Among the other two methods, the C MSAVI2 was found to be more consistent than the C NDVI1 method, but both methods lead to over-prediction of annual soil loss rate and therefore need to be reconsidered before applied in the RUSLE.